Analisis Pengaruh Pembangunan Kek Kendal Terhadap Tingkat Pengangguran Terbuka di Wilayah Kedungsepur, Jawa Tengah: Pendekatan Difference-In-Difference (DID) - Purnomosidi, Romanus Yoseph Kun Haribowo; Nurhasanah, Aswanda Talitha; Banowaty, Damay Ajeng; Rahmadanti, Navinda Hanin; Indrafarras, Rakha Abiyyu; Pratiwi, Ratih Arum; Pramesti, Ustania Hepy Yuli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to evaluate the impact of the Kendal Special Economic Zone (SEZ) development on the open unemployment rate (OUR) in the Kedungsepur region of Central Java, Indonesia. As part of the government’s strategy for industrial and regional economic development, the Kendal SEZ is expected to generate employment and improve local livelihoods. This research applies the Difference-in-Difference (DiD) approach using secondary data from the Central Bureau of Statistics. The key variables include OUR as the outcome, SEZ status as the treatment, and several covariates such as regional GDP per capita, education level, and population density. The findings indicate that the development of the Kendal SEZ has not significantly reduced OUR in statistical terms. These results suggest that the establishment of industrial zones alone may not effectively reduce unemployment without improved workforce readiness and inclusive development strategies.